2017
DOI: 10.1038/cddiscovery.2017.55
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli O157:H7 suppresses host autophagy and promotes epithelial adhesion via Tir-mediated and cAMP-independent activation of protein kinase A

Abstract: Autophagy is a pivotal innate immune response that not only degrades cytosolic components, but also serves as one of the critical antimicrobial mechanisms eliminating intracellular pathogens. However, its role in host defense against extracellular pathogens is largely unknown. Here we showed that E. coli O157:H7 altered autophagy to evade host defense and facilitate adhesion. Enhancing host cell autophagy with tumor necrosis factor (TNF), host starvation or rapamycin reduced the adherence of E. coli O157:H7 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 54 publications
1
14
0
Order By: Relevance
“…We observed a robust PKA activation in response to E. coli O157:H7 infection but not in tir deletion mutant (Δ tir ) strain infected cells, indicating Tir mediated PKA activation. We further showed that PKA activation was essential for E. coli O157:H7-induced autophagy inhibition, blocking PKA abolished E. coli O157:H7 ability to inhibit autophagy 6 . Correspondingly, cholera toxin and edema toxin from Vibrio cholerae and Bacillus anthracis , respectively, induce PKA hyperactivation and reduce autophagosome formation 8 .…”
Section: Introductionmentioning
confidence: 75%
See 3 more Smart Citations
“…We observed a robust PKA activation in response to E. coli O157:H7 infection but not in tir deletion mutant (Δ tir ) strain infected cells, indicating Tir mediated PKA activation. We further showed that PKA activation was essential for E. coli O157:H7-induced autophagy inhibition, blocking PKA abolished E. coli O157:H7 ability to inhibit autophagy 6 . Correspondingly, cholera toxin and edema toxin from Vibrio cholerae and Bacillus anthracis , respectively, induce PKA hyperactivation and reduce autophagosome formation 8 .…”
Section: Introductionmentioning
confidence: 75%
“…The ER stress sensor inositol-requiring enzyme 1α (IRE1α) is one of the mediators of UPR and has been implicated in ER stress-induced autophagy 11 . In our recent publication, upon E. coli O157:H7 infection, IRE1-α was decreased 6 , which may reduce autophagy-induced cell death and benefit bacterial survival. Accumulating studies have indicated that autophagy-induced cell death is a host strategy to inhibit bacterial replication.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Given that pathogen infections represent one of the major threats to the health of animals and human beings, thus, autophagy pathway is necessary to outcome host-microbe interactions. For example, E. coli O157:H7 dampens autophagy via a Tir-dependent pathway mechanism while autophagy activation suppresses the adhesion of E. coli O157:H7 to intestinal epithelial cells [ 25 ]. Moreover, recent evidence highlighted the cross-talk between autophagy and NLRP3 inflammasome activation [ 26 ].…”
Section: Introductionmentioning
confidence: 99%